Contribution of Two Different Packaging Material to Microbial Contamination of Peaches: Implications in Their Microbiological Quality - Patrignani, Francesca; Siroli, Lorenzo; Gardini, Fausto; Lanciotti, Rosalba (Frontiers in Microbiology, 2016)
Aim of this work was understanding the microbial transfer dynamics from packaging to packed peaches in relation to the packaging used. Method and Results: A challenge test was performed, inoculating Escherichia coli, Pseudomonas spp. and Saccharomyces cerevisiae on cardboards and RPC (Reusable Plastic Containers), and monitoring their cell loads on fruits according to a probabilistic model and a Response Surface Methodology in relation to several independent variables (number of fruit lesions, fruit temperature storage and commercialization time). The data recorded on packed peaches for Pseudomonas and S.cerevisiae were modelled to fit the second order model to study the main, interactive and quadratic effects of the independent variables on the cell loads of target microorganisms as well as on the shelf-life of the fruits in relation to packaging material used. The data collected for E. coli were codified as presence (1) or absence (0) and modelled with a logistic regression analysis to assess the probability of E. coli transferring from packaging to fruits in relation to the adopted variables. The data showed a higher contamination frequency of the fruits packed in plastic than in cardboard. Increasing the storage temperature and the number of lesions, the probability of transferring of E. coli from packaging materials to fruits increased, independently on commercialization time or packaging used. For Pseudomonas, the contamination levels detected on fruits packaged in plastic were significantly higher compared to those found on fruits packed in cardboard, independently on the considered variables. The polynomial equations showed the S. cerevisiae cell loads of fruits stored in plastic was positively affected by the quadratic term of temperature. Conclusions: the use of cardboard, compared to plastic, can significantly reduce the potential of microbial transferring from packaging to fruits. The probabilistic and kinetic models used showed a higher microbiological qualities of peaches stored in cardboard boxes, independently on the independent variables considered. The best performances of cardboard, compared to plastic, was probably due to its capability to entrap microbial cells. Significance and Impact: cardboard reduces fruit contamination and increases their shelf-life with positive fallouts on fruit shelf-life and all the logistic and distribution chain.